2H NMR lineshapes of immobilized uniaxially oriented membrane proteins - Ulrich, A; Watts, A (1993)
As a method for the structure determination of integral membrane proteins or other large macromolecular complexes, a solid state 2H NMR approach is presented, capable of measuring the orientations of individual chemical bond vectors. In an immobilized uniaxially oriented sample, the bond angle of a deuterium-labeled methyl group relative to the axis of ordering can be calculated from the quadrupole splitting in the "zero-tilt" spectrum where the sample normal is aligned parallel to the spectrometer field direction. However, since positive and negative values of this splitting cannot be distinguished, there may appear to be two solutions, of which only one describes the correct molecular geometry. We show that it is possible to determine the bond angle uniquely between 0° and 90°, by analysing the lineshapes of a tilt series of spectra acquired over different sample inclinations. The lineshape equation describing such oriented 2H NMR spectra will be derived (for asymmetry parameter η = 0) and discussed, with an illustration of the various linebroadening effects from which the orientational distribution function in the macroscopically ordered system can be determined. This strategy is then applied to specifically deuterium-labelled retinal in dark-adapted bacteriorhodopsin, prepared in a uniaxially oriented sample from purple membrane fragments. From the quadrupole splitting in the zero-tilt spectrum and by lineshape simulations, the deuteromethyl group at C20 on retinal is found to make an angle of 32° ± 1° with the membrane normal, and the sample mosaic spread to be around ± 8°. The resulting orientation of retinal is in excellent agreement with its known structure in bacteriorhodopsin, and together with the results on other methyl groups it will be possible to construct a detailed picture of the chromophore in the protein binding pocket. © 1993.